Effect of montelukast on polymorphonuclear leukocyte functions in asthmatic patients - (:unkn) unknown (ELSEVIER, 2003)
Leukotriene receptor antagonists are being used widely in the treatment of bronchial asthma. They have been shown to possess anti-inflammatory properties, but there is no sufficient data about their effects on polymorphonuclear leukocyte functions. The aim of this study was to investigate the effects of montelukast, a specific cysteinyl leukotriene-1 receptor antagonist, on human polymorphonuclear leukocyte (PMN) functions (phagocytic and intracellular killing activity) in asthmatic patients. Fifteen mild to moderate asthmatic patients were included in the study. They were treated with montelukast (10 mg/day per os) in addition to their previous medications for 2 weeks. Whole blood samples of patients were taken before and after this treatment period. Phagocytic activities and intracellular killing activities of polymorphonuclear leukocytes isolated from whole blood samples were tested by using appropriate technics. Phagocytic and intracellular killing activities of PMNs were significantly increased (p < 0.001, p < 0.05) by montelukast compared to those before treatment. These results show that montelukast has an enhancing effect on PMN functions in asthmatic patients. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: montelukast; polymorphonuclear leukocytes; asthma; allergic inflammation; LEUKOTRIENE RECEPTOR ANTAGONIST; EOSINOPHILIC INFLAMMATION; INHALED BECLOMETHASONE; ORAL MONTELUKAST; THERAPY; ANTIBIOTICS; INFECTIONS; PLACEBO